Prevalence of biofilm and beta-lactamase producing Staphylococcus in nasal and throat isolates from healthy volunteers: A medical alert - Devapriya, F; Sajith, P; Ranganathan, R; Shanmugam, J (Nepal Journal of Medical Sciences, 2015)
Background: The Staphylococci species are the predominant inhabitants of the nose and throat as normal flora, they are now becoming a threat due to their capacity to produce biofilm. Biofilm related infections are difficult to be treated unless it is diagnosed early. The aim was to study the prevalence of biofilm and beta-lactamase production in Staphylococcus isolates from nasal and throat mucosa in healthy volunteers. Methods: Staphlococcal isolates were collected from nasal and throat swabs of 100 healthy volunteers at Gulf Medical University and Gulf Medical College Hospital, Ajman, UAE. Staphylococcus aureus or Coagulase Negative Staphylococcus (CoNS) was classified from growth on Mannitol Salt Agar and tube coagulase test. Biofilm production detected by Christensen’s tissue culture plate and Congo red agar methods. Betalactamase production among biofilm producers identified by iodometric tube method. Results: Among 100 Staphylococcus isolates, 41 were Staphylococcus aureus of which 61% were biofilm producers of which 46.3% were betalactamase positive. Among the 59 CoNS isolates, 64.4% were biofilm producers of which 30.5% were beta-lactamase positive. Predominance of nasal Staphylococcal isolation observed among males at the age group of <20 years. Conclusion: Biofilm-producing Staphylococcus inhabits the nasal and throat mucosa of healthy individuals. Beta-lactamase production was higher in Staphylococcus aureus positive for biofilm producers as compared to CoNS. Transmission of these biofilm producers with drug resistance factors from the healthy individuals to high risk patients with indwelling devices need to be considered. Nepal Journal of Medical Sciences Vol.3(2) 2014: 79-83